Roles of maximal strength and rate of force development in maximizing muscular power - Taber, C.; Bellon, C.; Abbott, H.; Bingham, G. E. (Strength and Conditioning Journal, 2016)
This brief review encompasses the role of maximal strength and rate of force development in the production of muscular power. It begins with the investigation of power output and its importance for sport. After this basis for power production, this review examines both maximal strength and rate of force development effects on the development of optimal power output. Finally, a rational why maximizing rate of force development during the competition season to achieve success in sport is provided.